Effects of salivary thiocyanate levels on oral mucosa in young adult smokers: A biochemical and cytological study - Prakruthi, BV (J Oral Maxillofac Pathol, 2018)
BACKGROUND AND OBJECTIVES: Cigarette smoking is one of the major global health issues. Accurate measurement of smoking is essential for accepting patterns of adolescent smoking behavior and for the evaluation of health education programs aimed at reducing or preventing the habit. The aim of the present study was to estimate and compare the salivary thiocyanate levels in young adult smokers and nonsmokers and also to evaluate and correlate the cellular and nuclear changes in cytological smears with salivary thiocyanate levels. MATERIALS AND METHODS: The study included a total of 70 individuals in the age range of 18–25 years comprising of 35 smokers and 35 nonsmokers. A volume of 2 ml unstimulated whole saliva samples were collected by spitting method and were carried in a vaccine carrier with ice pack to the laboratory to avoid biochemical changes. Each sample was analyzed on the same day of collection by spectrophotometric method. In addition, cytosmears were prepared using Cytobrush(®) plus and stained with rapid Papanicolaou stain for cytological evaluation. RESULTS: Salivary thiocyanate levels were significantly higher in smokers than nonsmokers. When these levels were compared with pack-years, there was a progressive significant increase in salivary thiocyanate levels as the pack-years increased. Duration of habit showed no statistically significant effect on salivary thiocyanate levels. Cytological evaluation revealed increase in nuclear-cytoplasmic area ratio and number of micronuclei in smokers than nonsmokers. The correlation between salivary thiocyanate levels and cytological changes showed insignificant result. CONCLUSION: Salivary thiocyanate levels were significantly higher in smokers than controls and showed significant correlation with the number of pack years. Although the present study failed to reveal any significant correlation between salivary thiocyanate level and cytological alterations, few early alterations in the oral mucosa even in the absence of clinical manifestations were detected by exfoliative cytology. Salivary thiocyanate determination is a safe, inexpensive, noninvasive method to differentiate early smokers from nonsmokers.